Non-aqueous solutions-- 5 : plenary and section lectures presented at the fifth International Conference on Non-aqueous Solutions, Leeds, England, 5-9 July 1976 - Gill, J. B. (Pergamon Press, 1977)
Non-Aqueous Solutions - 5 is a collection of lectures presented at the Fifth International Conference on Non-Aqueous Solutions held in Leeds, England, on July 5-9, 1976. The papers explore reactions in non-aqueous solutions as well as the thermodynamic and kinetic properties of non-aqueous solutions. Examples of the use of spectroscopic techniques are presented, and solutions in molten salts are given. Metals in solution and liquid metal solutions are also considered. This book is comprised of 12 chapters and begins with a review of a general scheme which considers the species formed by cation.